Token Economy as the Intervention of Self-Injurious Behavior in Students with Mental Retardation - Beti Malia Rahma Hidayati; Octari Rohmah (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2022)
Self-injury in children with mental retardation is caused by their inability to express their feelings and emotions. This study aimed to describe self-injury experienced by students with mental retardation and examine the influence of the token economy on the self-injury of students with mental retardation at the special school (SLB) Bhakti Pemuda, Tamanan, Kediri. The study used a quantitative approach with experimental methods based on the pre-experimental design with the one-group pretest posttest design. Based on the exclusion criteria, there were five children experienced mental retardation, and they were selected using the purposive sampling technique. The researchers conducted a pre-test, treatment, and post-test. The data was analyzed using the IBM SPSS 20 program. The results showed that the self-injury in students with mental retardation at SLB Bhakti Pemuda, Tamanan, Kediri included hitting themselves, hitting tables and chairs, running, pulling their hair, hurting themselves using pencils, experiencing anxiety continuously, and being unable to control emotions.